The Effectiveness of Parent-Based Behavioral Intervention on Industrial Snack Requests and Parent–Child Conflict in Obese and Overweight Children - Bidgolian, Mohammadreza; Jahan, Faezeh; Sabahi , Parviz; Asadzadeh, Hassan (Mental Health and Lifestyle Journal, 2024)
The aim of this study was to investigate the effectiveness of parent-based behavioral intervention on industrial snack requests and parent–child conflict in obese and overweight children. The research method was quasi-experimental with a pretest–posttest and follow-up design using a control group. The statistical population included all mothers of obese and overweight children aged 4 to 6 years in Tehran and their children. The sample consisted of 38 mother–child dyads selected from the statistical population through purposive sampling and assigned to experimental and control groups. For the experimental group, the parent-based behavioral intervention was implemented in eight one-hour sessions, while the control group remained on the waiting list. The research instruments included the Children’s Industrial Snack Request Frequency Checklist and the Parent–Child Relationship Questionnaire (Pianta, 1994). The results indicated that parent-based behavioral intervention had a significant effect on simple industrial snack requests, insistent or conflict-related industrial snack requests, and parent–child conflict in the posttest and follow-up stages. The findings of this study provide useful information regarding parent-based behavioral intervention, and psychologists and psychiatrists may employ this approach to improve nutritional problems and parent–child conflict.